Dual Lp affine isoperimetric inequalities. (19th September 2006) - Lin, Si; Bin, Xiong; Wuyang, Yu
Abstract : We establish some inequalities for the dualp -centroid bodies which are the dual forms of the results by Lutwak, Yang, and Zhang. Further, we establish a Brunn-Minkowski-type inequality for the polar of dualp -centroid bodies.